Paleoproteomics of the Dental Pulp: The plague paradigm - Barbieri, Rémi (PLoS One, 2017)
Chemical decomposition and fragmentation may limit the detection of ancient host and microbial DNA while some proteins can be detected for extended periods of time. We applied paleoproteomics on 300-year-old dental pulp specimens recovered from 16 individuals in two archeological funeral sites in France, comprising one documented plague site and one documented plague-negative site. The dental pulp paleoproteome of the 16 teeth comprised 439 peptides representative of 30 proteins of human origin and 211 peptides representative of 27 proteins of non-human origin. Human proteins consisted of conjunctive tissue and blood proteins including IgA immunoglobulins. Four peptides were indicative of three presumable Yersinia pestis proteins detected in 3/8 dental pulp specimens from the plague-positive site but not in the eight dental pulp specimens collected in the plague-negative site. Paleoproteomics applied to the dental pulp is a new and innovative approach to screen ancient individuals for the detection of blood-borne pathogens and host inflammatory response.